Authority of the Dispute Council in the Resolution of Construction Disputes in Indonesia - Vidyapramatya, Nurindria Naharista; Latifah, Emmy; Farida, Elfia; Tigor, Antonius Alexander (LAW REFORM, 2023)
The Dispute Council is a construction dispute resolution forum mandated by Law Number 2 of 2017 concerning Construction Services. The existence of the Dispute Council as a construction dispute resolution forum is actually not much different from other alternative dispute resolution forums, such as negotiation, mediation, and arbitration. However, the Construction Services Law mandates that a Dispute Council be formed by the parties simultaneously with the preparation of a construction work contract. In practice, decisions made by the Dispute Council are often not final and binding if one of the parties is not willing to implement the decision of the Dispute Council. This study aimed to compare the effectiveness of the authorities between the Dispute Council and other alternative dispute resolution forums. This research was normative research. The data used were secondary data consisting of primary, secondary, and tertiary legal materials. The data collection technique used literature study, and the data analysis technique used qualitative analysis. The results of the research show that the dispute resolution process with the Dispute Council is ineffective because it takes a long time. Parties who do not want to implement the decision of the Dispute Council will continue the dispute resolution process to arbitration. In fact, when the arbitration process fails, the dispute is submitted to court. This situation becomes more effective and saves time when the resolution of construction disputes directly uses arbitration without going through the Dispute Council first.